Asset divestitures and corporate operational returns: an agency theory perspective on Malaysian public-listed companies - Ym, Janice Lee; Nor, Fauzias Mat; Alias, Norazlan (International Journal of Strategic Property Management, 2013)
Divestitures of property, plant and equipment (PPE) assets are a common form of corporate restructuring. However, divesting companies do not necessarily attain improved post-divestiture shareholder wealth. Studies show company characteristics and use of divestiture proceeds may influence divestiture outcomes. This paper attempts to determine these divesting company characteristics and use of proceeds associated with improved shareholder wealth based on the Agency Theory. A sample of Malaysian public-listed companies that divested assets within 2002–2005 is used. Logistic regression segregates these companies based on their industry-adjusted operational returns. Companies that improve post-divestiture operational performance require urgent pay out motives to divest. Companies with deteriorated post-divestiture performance divest without urgent pay out motive and tend to retain proceeds. This suggests agency problem of managerial discretion in asset divestitures. In asset selection, divestitures of larger and more inefficient assets were found associated with improved company performance. Malaysian companies prefer divesting assets related to their core businesses indicating a diversified company structure is more beneficial than a focused structure in developing countries. First Publish Online: 19 Dec 2013